The Relationship Between Family Support and Quality of Life of Patients with Diabetes Mellitus in the Melati Room of Vita Insani Hospital Pematangsiantar - Muharti Sanjaya (International Journal of Public Health Excellence (IJPHE), 2023)
Family support is needed to provide a person's physical and psychological comfort when experiencing illness. Family support is very important for the survival of DM sufferers, so that with good family support, the quality of support will be good. This study aims to determine the relationship of family support to the quality of life of DM sufferers. This is a quantitative study using a cross-sectional design approach. The sampling technique used was accidental sampling. This research was conducted in July-August 2019 in the Melati room at Vita Insani Hospital, Pematangsiantar. Hypothesis analysis used the 2x2 chi-square test. middle class, income Rp. 750 000.00 and Rp. 750,000.00 Rp. 1452 400.00, suffering from DM for an average of 6 years. Families with DM sufferers, mostly in the middle adult age, have a relationship between children and sufferers of DM, female sex. 42 respondents (80.8%) 37 respondents (71.2%) had a poor quality of life. There was a relationship between family support and the quality of life of DM sufferers (p-0.046). Family support was related to the quality of life of DM sufferers. Nurses should involve families of DM sufferers in providing nursing care. Further research should examine the analysis of the factors that most influence the quality of life of DM sufferers and conduct research in a hospital.